Effect of shot peening on fatigue behavior of AISI 4340 in different loading conditions - Harada, D. T. [UNESP]; Cindra, Fonseca M.P. [UNESP]; Torres, M. A.S.; Baptista, C. A.R.P. (Trans Tech Publications, 2016)
Shot peening is a method widely used to improve the fatigue strength of materials, through the creation of a compressive residual stress field (CRSF) in their surface layers. In the present research the gain in fatigue life of AISI 4340 steel, obtained by shot peening treatment, is evaluated under the three different hardnesses used in landing gear. Rotating bending fatigue tests and alternating tension tests were conducted and the CRSF was measured by x-ray tensometry prior and after interrupted fatigue tests. The evaluation of fatigue life after shot peening in relation to the relaxation of CRSF, of the crack initiation sites and surface roughness is done.
Keywords: AISI 4340 steel; Fatigue; Residual stress; Shot peening